KOMUNIKASI BISNIS - Muh. Ruslan Abdullah (AL TAJDID, 2010)
Communication and business will be discipline science very differ but communication of vital importance in the world of business. somebody success in the world of business is determined how well they do communication, as does in concerned in the world of effort/ when not do communication difficult to compete in the world of business, because in the world of business is used causality law.